Open laryngectomy: Clinical experience - L. G. Kozhanov; A. M. Sdvizhkov; A. L. Kozhanov; S. A. Kravtsov; M. T. Bekov; M. V. Mulyarets (Опухоли головы и шеи, 2018)
Introduction. The problem of treatment and rehabilitation of patients with laryngeal cancer has been a complicated and controversial one.Important conditions for selection of the type and scale of functionally sparing surgical intervention are accurate preoperative diagnosis of advancement of the tumor and oncological appropriateness of the intervention. Currently, the problem of single-step reconstruction of lost laryngeal functions after organ-preserving surgeries remains open. For this purpose, researchers use both auto-/homografts and endoprosthetics made of various materials. In some cases, endoprosthetics in lyrengectomy didn’t allow to restore laryngeal lumen due to granulation tissue, cicatricial stenosis, laryngotracheomalacia.The study objective is to increase treatment and rehabilitation effectiveness in patients with laryngeal cancer after open laryngectomy.Materials and methods. Our experience is based on open laryngectomies in 86 patients performed at the Clinical Oncology Dispensary No. 1 of the Moscow Healthcare Department in the period from 2011 to 2014. Primary laryngeal cancer was diagnosed in 84 (97.7 %) patients, recurrent laryngeal cancer after a full course of radiation therapy – in 2 (2.3 %) patients. Vertical laryngectomy was performed in 74 patients, horizontal – in 12 patients.Vertical laryngectomies were performed for tumors located near the vocal and vestibular flaps, anterior commissure, subglottis, laryngeal sinus;horizontal for tumors located near the epiglottis, vestibular flaps, vallecula, root of the tongue if arytenoids were intact and vocal cords were mobile. In the postoperative period, an important factor was restoration of the organ’s function through early rehabilitation of respiratory, vocal, and protective functions. Evaluation of the laryngeal lumen was performed using endoscopic examination. Any diagnosed ligatures, granulation tissue, scars were resected. Prior to decannulation, ultrasound examination of the larynx was performed. Effectiveness of vocal function restoration was evaluated using computer acoustic analysis of the voice.Results. Restoration of the lost laryngeal functions after organ-preserving open laryngectomies in patients with laryngeal cancer is achieved through reconstruction of the remaining parts of the organ, formation of an adequate lumen for breathing through postoperative endoscopic correction, and early rehabilitation of respiratory, vocal, and protective function.Conclusion. Open laryngectomies with restoration of the remaining parts and single-step reconstruction of the lumen with an endoprosthesis, as well as subsequent combined treatment, allowed to restore respiratory function in 93.1 % patients, vocal function – in 91.9 % patients.